Shared values and beliefs of classroom teachers who operate as transformative intellectuals in online communities. Issue 3 (3rd July 2021) - Clancy, Zachary; Ku, Heng-Yu
ABSTRACT: Online communities have the potential to help teacher education programs inform and prepare future teachers to teach children equitably and confront social injustices. The purpose of this study was to gain a better understanding of the shared values and beliefs of teachers who operate as transformative intellectuals in online places. Findings were categorized based on the topic domains of interview questions. The study included six participants from two social-justice and human-rights oriented online communities of teachers, #SaturdaySchool and #EduColor. Three data sources, a demographic survey questionnaire, individual interviews, and fieldnotes, were used to answer the research question. Findings suggested that participants in both communities think that teachers should have access to and participate in online places in which teachers, teacher-educators, and activists engage in social-justice and human-rights work. The findings demonstrated that participants thought it was essential to have a venue for ongoing and reflective conversations. Additionally, the findings suggest that participants in both groups view their communities as places to challenge what they have learned in the past, connect with other teachers, and share professional experiences. Participants also view both communities as sources of encouragement and places to feel vulnerable.